A comparison of FORMOSAT-3/COSMIC radio occultation and ionosonde measurements in sporadic E detection over mid- and low-latitude regions - Sobhkhiz-Miandehi, S.; Yamazaki, Y.; Arras, C.; Themens, D. (Frontiers in Astronomy and Space Sciences, 2023)
The investigation of Sporadic E or Es layers typically relies on ground-based or satellite data. This study compares the Es layers recorded in ionograms with those detected using GNSS L1 signal-tonoise ratio data from FORMOSAT-3/COSMIC radio occultation at mid and low latitudes. GPS radio occultation measurements of Es layers, during 11-year time span of 2007 to 2017, within a 2° latitude × 5° longitude grid around each ionosonde site are compared to the Es recordings of the ionosonde. By comparing multi-year radio occultation data with recordings from six ionosonde stations at mid and low latitudes, it was discovered that at least 20% of the Es layer detection results between each ionosonde and its crossing GPS radio occultation measurements did not agree. The results show that the agreement between the two methods in Es detection is highly dependent on the season and local time. This study suggests that Es layer recordings from ground-based ionosonde observations have the best agreement with the Es layers detected by radio occultation data during daytime and local summers. The difference in the Es detection mechanisms between the two methods can explain the inconsistency between Es events measured by these two methods. The detection of Es layers in ionograms relies on the high plasma concentration in the E region, whereas signal scintillations caused by a large vertical gradient of the plasma density in the E region are considered as a sign of Es occurrence in satellite techniques.